Shenmai Injection Improves Energy Metabolism in Patients With Heart Failure: A Randomized Controlled Trial - Wang, Shao-mei; Ye, Li-fang; Wang, Li-hong (Frontiers in Pharmacology, 2020)
Background: In recent years, the application of Shenmai (SM) injection, a traditional Chinese medicine (TCM), to treat heart failure (HF) has been gradually accepted in China. However, whether SM improves energy metabolism patients with HF has not been determined due to the lack of studies with high qualities. We aimed to investigate the influence of SM on energy metabolism in patients with HF. Methods: This single-blind, controlled study randomly assigned 120 eligible patients equally into 3 groups receiving SM, trimetazidine (TMZ) or control in addition to standard medical treatment of HF for 7 days. The primary endpoints were changes of free fatty acids (FFAs), glucose, lactic acid (LA), pyroracemic acid (pyruvate, PA) and branched chain amino acids (BCAAs) in serum. Secondary outcomes included the New York Heart Association (NYHA) functional classification, TCM syndrome score (TCM-s), left ventricular injection fraction (LVEF), left ventricular internal diastolic diameter (LVIDd), left ventricular internal dimension systole (LVIDs) and B-type natriuretic peptide (BNP). Results: After treatment for 1 week, the NYHA functional classification, TCM-s and BNP level gradually decreased in patients from all 3 groups, but these metrics were significantly increased in the patients of SM group compared with those from TMZ and control groups (p<0.05). Moreover, the energy metabolism was improved in NYHA III~IV patients of SM group compared with those in the TMZ and control groups, as evidenced by the changes of serum levels of FFA, LA, PA and BCAA. Conclusions: Integrative treatment with SM in addition to standard medical treatment for HF was associated with improved cardiac function as compared to standard medical treatment alone. The benefit of SM in HF may be related to the improvement of energy metabolism, which seems to be more remarkable than treatment with TMZ.